Expression of Urea Transporter B in Normal and Injured Brain - Huang, Boyue; Wang, Hongkai; Zhong, Dandan; Meng, Jia; Li, Min; Yang, Baoxue; Ran, Jianhua (Frontiers in Neuroanatomy, 2021)
Urea transporter B (UT-B) is a membrane channel protein widely distributed in mammals and plays a significant physiological role by regulating urea and water transportation in different tissues. More and more studies have found that UT-B is related to neurological diseases, including myelinopathy and depression. Urea is accumulated in the brains of UT-B knockout mice, the synaptic plasticity of neurons is reduced, and the morphology and function of glial cells are also changed. However, the distribution and expression change of UT-B remain unclear. The purpose of this study was to determine the expression characteristics of UT-B in brain. Through single-cell RNA sequencing, UT-B was found to express universally and substantially throughout the various cells in central nervous system except endothelial and smooth muscle cells. UT-B was detected in third cerebral ventricular wall, granule cell layer of the dentate gyrus and other parts of hippocampal, cerebral cortex, substantia nigra, habenular and lateral hypothalamic nucleus by immunohistochemistry. Compared with the membrane expression of UT-B in glial cells, the subcellular localization of UT-B is in the Golgi apparatus of neurons. Further, the expression of UT-B was regulated by osmotic pressure in vitro. In the experimental traumatic brain injury model (TBI), the number of UT-B positive neurons near the ipsilateral cerebral cortex increased first and then decreased over time, peaking at 24th hour. We inferred that change in UT-B expression after TBI was adaption to changed urea level. The experimental data suggest that UT-B may be a potential target for the treatment of TBI and white matter edema.